Home and School Environmental Influences on Adolescents' Sociopolitical Group Participation: Implications for Increasing Youth Involvement. Issue 7 (September 2019) - Curtis, Christopher A.
The potential benefits associated with sociopolitical group involvement for participating youth have been well documented in the existing literature. Yet, little is known about what motivates voluntary participation in such programs among youth. The purpose of this study is to explore what environmental factors influence youth civic engagement through participation in sociopolitical groups (e.g., service-learning or community service programs). To do this, several independent variables captured in The Commission on Youth Voting and Civic Knowledge Youth Post Election Survey 2012 dataset and the respondents' reported participation in social or political groups while in high school were observed. Binary and ordinal logistic regression modeling were used to analyze the data. The results indicate that several factors in the home and school environment are related to an increased probability of youth joining a sociopolitical group at school, away from school, or both. These findings suggest that the messages crafted to encourage youth participation in sociopolitical groups should account for the demographic (i.e., racial, gender, and cultural) and experiential (i.e., civics education quality) differences present within the target population.